2013
DOI: 10.1242/bio.20134457
|View full text |Cite
|
Sign up to set email alerts
|

Primary ciliogenesis requires the distal appendage component Cep123

Abstract: SummaryPrimary cilium formation is initiated at the distal end of the mother centriole in a highly co-ordinated manner. This requires the capping of the distal end of the mother centriole with a ciliary vesicle and the anchoring of the basal body (mother centriole) to the cell cortex, both of which are mediated by the distal appendages. Here, we show that the distal appendage protein Cep123 (Cep89/CCDC123) is required for the assembly, but not the maintenance, of a primary cilium. In the absence of Cep123 cili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
102
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(112 citation statements)
references
References 60 publications
7
102
0
1
Order By: Relevance
“…Multiple components of the centriolar distal appendages have been identified recently, including Ccdc41, Cep89, Sclt1, and Fbf1 (9,11,12,14). To study whether C2cd3 regulates the recruitment of additional distal appendage components, we transiently expressed GFP-tagged Ccdc41, Sclt1, Cep89, and Fbf1 in wild-type and C2cd3 GT mutant cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple components of the centriolar distal appendages have been identified recently, including Ccdc41, Cep89, Sclt1, and Fbf1 (9,11,12,14). To study whether C2cd3 regulates the recruitment of additional distal appendage components, we transiently expressed GFP-tagged Ccdc41, Sclt1, Cep89, and Fbf1 in wild-type and C2cd3 GT mutant cells.…”
Section: Resultsmentioning
confidence: 99%
“…jax.org/marker/MGI:2141942), an inhibitor of ciliogenesis, from the distal end of the mother centriole (10). Recent studies have also suggested that components of the distal appendages are essential for docking ciliary vesicles to the mother centriole (9,(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…Vesicle docking at the mother centriole requires the presence of distal appendage components, including the proteins Cep164 and Cep123 (Schmidt et al, 2012;Sillibourne et al, 2013;Tanos et al, 2013). As assessed by TEM, distal appendages were present in WDR8-depleted cells (Fig.…”
Section: Wdr8 Is Required For Targeting Of Rab8 and Arl13b To The Basmentioning
confidence: 94%
“…Distal appendage proteins, including Cep164 and Cep123 (also known as Cep89), have been reported to be indispensable for this initial step of ciliary membrane biogenesis (Schmidt et al, 2012;Tanos et al, 2013;Joo et al, 2013;Sillibourne et al, 2013;Burke et al, 2014;Ye et al, 2014). Moreover, a cascade of small GTPases regulates vesicle docking and fusion at the mother centriole.…”
Section: Introductionmentioning
confidence: 99%
“…Ces fibres de transition et la zone de transition à la base de l'axonème forment une structure agissant comme un filtre moléculaire qui contrôle le passage des protéines vers ou en dehors du cil. La composition des appendices distaux vient d'être récemment déterminée [11] : les protéines qui les constituent (PAD) ( Figure 1B) sont requises pour la formation des cils primaires [11][12][13][14][15]. CEP83 (centrosomal protein of 83-kDa)/CCDC41 (coiled-coil domain containing 41) joue un rôle central car elle est requise pour l'ancrage de toutes les autres protéines des appendices distaux au centriole père [11].…”
Section: Les Appendices Distauxunclassified